Analysis Of The Effect Of Fuel Additive Variations On Power, Torque And Top Speed In Matic Motorcycles - Wendi Leo Agustin; Donny Fernandez; R Chandra (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2021)
This study discusses variations in the use of carbon cleaner additives for Power, Torque and Top Speed ​​produced by Beat motorbikes in 2016 using a mixture of 75ml and 150ml additives. The purpose of this study is to analyze how much power, torque and top speed the vehicle will get if the fuel is mixed using carbon cleaner. This type of research is experimental research. The object of this research is a Honda Beat motorcycle in 2015. At the initial starting without giving a mixture of additives Power, Torque and Top Speed ​​produced respectively 6.23 kw, 6.38 Nm and 52.53 Km / hour, the treatment using carbon cleaner additives as much as 75 ml Power, Torque and The resulting top speed of each mixture is 6.74 kw, 6.84 Nm, and Top Speed ​​53.82 km / hour. Whereas in the use of carbon cleaner additives as much as 150ml, the increase in Power, Torque and Top Speed ​​respectively was 6.47 kw, 6.41 N.m and Top Speed ​​52.93 km / hour. After going through a comparative test using the t test with a significant level of 5%, it can be said that the increase in Power, Torque and Top Speed ​​without treatment with the treatment of 75ml and 150ml is not significant. Penelitian ini membahas tentang variasi penggunaan zat aditif carbon cleaner terhadap Daya, Torsi dan Top Speed yang dihasilkan oleh sepeda motor Beat tahun 2016 dengan menggunakan campuran zat aditif sebanyak 75ml dan 150ml. Tujuan Penelitian ini adalah Menganalisa berapa pengaruh Daya, Torsi dan Top Speed yang peroleh kendaraan yang apabila bahan bakar dicampurkan menggunakan carbon cleaner. Jenis Penelitian ini adalah penelitian eksperimen. Objek penelitian ini adalah sepeda motor honda Beat tahun 2015. Pada starting awal tanpa memberikan campuran zat aditif Daya, Torsi dan Top Speed yang dihasilkan masing-masing sebesar 6,23 kw, 6,38 N.m dan 52,53 Km/jam, pada perlakuan penggunaan zat aditif carbon cleaner sebanyak 75ml Daya, Torsi dan Top Speed yang dihasilkan masing-masing campuran sebesar 6,74 kw, 6,84 N.m, dan Top Speed 53,82 Km/Jam. Sedangkan pada penggunaan zat aditif carbon cleaner sebanyak 150ml peningkatan Daya, Torsi dan Top Speed masing-masing sebesar 6,47 kw, 6,41 N.m dan Top Speed 52,93 km/jam.